2017
DOI: 10.1111/jbi.13050
|View full text |Cite
|
Sign up to set email alerts
|

The loss of dispersal on islands hypothesis revisited: Implementing phylogeography to investigate evolution of dispersal traits in Periploca (Apocynaceae)

Abstract: Aim: The loss of dispersal on islands hypothesis (LDIH) posits that wind-dispersed plants should exhibit reduced dispersal potential, particularly if island populations are old. In this study, we tested this hypothesis using a detailed phylogeographical framework across different geographical scales. Location: Mainland and island areas of the Atlantic and Mediterranean regions, including Macaronesia (Canary Islands and Cape Verde) and Mediterranean islands in the strait of Sicily. Methods: Forty-five populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
72
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(77 citation statements)
references
References 46 publications
4
72
0
1
Order By: Relevance
“…A more recent study on animal species native to New Caledonia showed that there is a higher proportion of species with restricted ranges (≤5.2 km 2 ) in non‐endemic species (22%) than in endemic species (12%), suggesting that environmental dissimilarity may play an important role in their distribution (Caesar, Grandcolas, & Pellens, ). The role of environmental filtering in shaping island communities is gaining increasing support in the literature, while recent biogeographical and phylogenetical analyses in the Galápagos and Macaronesia have provided increasing evidence against the hypothesis of lesser dispersal ability in islands (Carvajal‐Endara, Hendry, Hendry, Emery, & Davies, ; García‐Verdugo, Mairal, Monroy, Sajeva, & Caujapé‐Castells, ).…”
Section: Discussionmentioning
confidence: 99%
“…A more recent study on animal species native to New Caledonia showed that there is a higher proportion of species with restricted ranges (≤5.2 km 2 ) in non‐endemic species (22%) than in endemic species (12%), suggesting that environmental dissimilarity may play an important role in their distribution (Caesar, Grandcolas, & Pellens, ). The role of environmental filtering in shaping island communities is gaining increasing support in the literature, while recent biogeographical and phylogenetical analyses in the Galápagos and Macaronesia have provided increasing evidence against the hypothesis of lesser dispersal ability in islands (Carvajal‐Endara, Hendry, Hendry, Emery, & Davies, ; García‐Verdugo, Mairal, Monroy, Sajeva, & Caujapé‐Castells, ).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, we compare the genetic structure of northwestern African and Macaronesian populations of P. laevigata obtained by García-Verdugo et al (2017) with wind connectivity between those areas computed with rWind. 2A, B, C in García-Verdugo et al 2017). 2A, B, C in García-Verdugo et al 2017).…”
Section: Example 3: Measuring Wind Connectivity Between Northwestern mentioning
confidence: 99%
“…In their research, García-Verdugo et al detected a close genetic relation between northwestern African populations, eastern Canary Islands populations and Cape Verde populations ( Fig. In this example we compute wind connectivity from locations sampled on the African mainland by García-Verdugo et al (2017) with their sampled islands of Fuerteventura (eastern Canary Islands), Gran Canaria and Tenerife (central Canary Islands), La Palma (western Canary Islands), and Santo Antão and Fogo (Cape Verde). In this example we compute wind connectivity from locations sampled on the African mainland by García-Verdugo et al (2017) with their sampled islands of Fuerteventura (eastern Canary Islands), Gran Canaria and Tenerife (central Canary Islands), La Palma (western Canary Islands), and Santo Antão and Fogo (Cape Verde).…”
Section: Example 3: Measuring Wind Connectivity Between Northwestern mentioning
confidence: 99%
See 2 more Smart Citations